Overcoming the Key Challenges to Establishing Vehicular Communication: Is SDN the Answer? - Yaqoob, Ibrar; Ahmad, Iftikhar; Ahmed, Ejaz; Gani, Abdullah; Imran, Muhammad; Guizani, Nadra (Institute of Electrical and Electronics Engineers, 2017)
Considerable development in software-based configurable hardware has paved the way for a new networking paradigm called software-defined vehicular networks (SDVNs). The distinctive features of SDN, such as its flexibility and programmability, can help fulfill the performance and management requirements for VANETs. Although several studies exist on VANET and SDN, a tutorial on SDVNs is still lacking. In this article, we initially investigate recent premier research advances in the SDVN paradigm. Then we categorize and classify SDVN concepts and establish a taxonomy based on important characteristics, such as services, access technologies, network architectural components, opportunities, operational modes, and system components. Furthermore, we identify and outline the key requirements for SDVNs. Finally, we enumerate and outline future research challenges.